FACTORS INFLUENCING THE USE OF ICT AMONG CASHEW NUT MARKETERS IN OYO STATE, NIGERIA - Mohammed, O. O.; Dickson, D.O.; Oke, S.O.; Akande, O.S.; Omonayin, M.A.; Owoyale, Y.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the factors influencing ICT usage among cashew nut marketers in Oyo and Ogbomosho Zones of Oyo State. A multi-stage sampling technique was used to select 200 respondents, and data were collected using structured questionnaires. Descriptive statistics and a multinomial logit model were used for analysis. Results revealed that marketers were predominantly middle-aged x=47.25, married 88.2, and experienced, with education significantly predicting ICT adoption. Mobile phones and WhatsApp remain the most used tools, while advanced technologies show low patronage. The model indicated that education level (p < 0.05) and cost of technology (p < 0.01) were the significant determinants of ICT usage, while credit access and social influence showed limited effects. The study concludes that education level and cost of technology were the significant factor s influencing the use of ICT among cashw farmers in the study area. . The study recommended the need to enhance ICT integration in the cashew marketing chain.